Unequal Inclusion: An Analysis of the Trajectory of Inequalities in Access, Use and Appropriation of the Internet in Brazil - Storino, Fabio; Senne, Fábio; Portilho, Luciana; Barbosa, Alexandre (Law, State and Telecommunications Review, 2020)
Purpose ”“ The paper aims at assessing the evolution of the digital divide in Brazil in the last decade from a multidimensional perspective, going beyond the issue of access. How have the inequalities in the use of Internet in Brazil varied through time? Methodology ”“ The paper investigates the relationship between individual socioeconomic characteristics and household characteristics, and the pattern of Internet access and use in Brazil using multivariate analysis, drawing on data from national ICT surveys between the years 2000 and 2019. Findings ”“ The results show that increasing access do not necessarily result in a more equitable adoption and use of available online resources. They highlight a persistent “digital elite” capable of a more sophisticated use of the Internet. The maintenance ”” and even the increase ”” of differences in the use of Internet is in line with part of the literature on digital inclusion. Practical Implications ”“ The study underscores the importance of developing methodological frameworks to better measure the digital divide, allowing it to be used as the independent variable in broader analyses of income inequality and access to public services, for instance. Additionally, the persistence of a "second level digital divide" in Brazil points to the need for policies that address the "digital skills gap" enabling the realization of the Internet’s potential to ease social disparities. Originality ”“ Despite the existing literature on the relationship between online inequalities and other kinds of inequalities, there are still few empirical studies, especially with a multidimensional perspective.